Abundance, origin, and phylogeny of plants do not predict community‐level patterns of pathogen diversity and infection. Issue 12 (18th May 2020) - Schmidt, Robin; Auge, Harald; Deising, Holger B.; Hensen, Isabell; Mangan, Scott A.; Schädler, Martin; Stein, Claudia; Knight, Tiffany M.
Abstract: Pathogens have the potential to shape plant community structure, and thus, it is important to understand the factors that determine pathogen diversity and infection in communities. The abundance, origin, and evolutionary relationships of plant hosts are all known to influence pathogen patterns and are typically studied separately. We present an observational study that examined the influence of all three factors and their interactions on the diversity of and infection of several broad taxonomic groups of foliar, floral, and stem pathogens across three sites in a temperate grassland in the central United States. Despite that pathogens are known to respond positively to increases in their host abundances in other systems, we found no relationship between host abundance and either pathogen diversity or infection. Native and exotic plants did not differ in their infection levels, but exotic plants hosted a more generalist pathogen community compared to native plants. There was no phylogenetic signal across plants in pathogen diversity or infection. The lack of evidence for a role of abundance, origin, and evolutionary relationships in shaping patterns of pathogens in our study might be explained by the high generalization and global distributions of our focal pathogen community, as well as the high diversity of our plant host community. In general, the community‐level patterns of aboveground pathogen infections have received less attention than belowground pathogens, and our results suggest that their patterns might not be explained by the same drivers. Abstract : We investigated the effects of plant abundance, origin, and phylogenetic community context on the diversity and infection levels of aboveground pathogens in a temperate grassland in the central United States. We found no relationship between host abundance, plant origin or phylogeny, and our observed infection levels. However, exotic host species harbored a more generalist pathogen community.